EKSPLORASI KONSEP FISIKA DARI KEARIFAN LOKAL TARIAN TORAJA PA’GELLU MENGGUNAKAN MODEL INKUIRI TERBIMBING - Tandipau, Aras; Tumangkeng, Jeane V; Umboh, Sixtus Iwan (LPPM Politeknik Saint Paul Sorong, 2024)
Physics learning is often faced with difficulties in understanding concepts that are difficult for students. Innovation in physics learning through local wisdom is a solution to make learning more relevant and interesting. This research aims to explore physics concepts in Toraja Pa'gellu dance using Guided Inquiry model. The qualitative research method was conducted at SMA Negeri 1 North Toraja with the subject of class XII IPA students. Data were collected through exploration sheets and analysed by data reduction, presentation, and conclusion drawing. The results showed an increase in students' ability to explore physics concepts in Pa'gellu dance after using the Guided Inquiry learning model. The physics concepts identified include speed, acceleration, force, moment of force, and other physical variables. Exploration of physics concepts in the local wisdom of Toraja Pa'gellu dance has a positive impact on students' understanding of physics concepts.